Proses berpikir siswa dalam menyelesaikan masalah barisan dan deret aritmatika - Anggita Febriliyani; Novisita Ratu (STKIP PGRI Banjarmasin, 2018)
this research is a qualitative descriptive which aims to analyze students thinking process in solving arithmetic sequence and series problems. Subject in this research were three grade XII students of SMA Negeri 1 Ambarawa on of academe year 2018/2019 is FHA as a high ability subject, AK as a medium ability subject, and WDR as a low ability subject. Data collecting methods are test, interview, and documentation. The result showed that in solving arithmetic sequence the first number problem all subjects used the conceptual thinking process while the second number arithmetic series problem the high subject used the conceptual thinking process and the medium and low subject used the process of using semiconceptual.